A bar and hinge model formulation for structural analysis of curved-crease origami. (November 2020) - Woodruff, Steven R.; Filipov, Evgueni T.
Highlights: A bar and hinge model is formulated to simulate folding and post-folding structural behaviors of curved-crease origami. Model stiffness is defined based on the geometric parameters of a flat fold pattern and the sheet material properties. The folded geometry and large deformations of real origami can be approximated well. The model is suitable for exploring the highly anisotropic stiffness characteristics of curved-crease origami. Abstract: In this paper, we present a method for simulating the structural properties of curved-crease origami through the use of a simplified numerical method called the bar and hinge model. We derive stiffness expressions for three deformation behaviors including stretching of the sheet, bending of the sheet, and folding along the creases. The stiffness expressions are based on system parameters that a user knows before analysis, such as the material properties of the sheet and the geometry of the flat fold pattern. We show that the model is capable of capturing folding behavior of curved-crease origami structures accurately by comparing deformed shapes to other theoretical and experimental approximations of the deformations. The model is used to study the structural behavior of a creased annulus sector and an origami fan. These studies demonstrate the versatile capability of the bar and hinge model for exploring the unique mechanical characteristics of curved-crease origami. The simulation codes for curved-crease origami are provided with this paper.